Synthesis and properties of bio-waste-based hydroxyapatite via hydrothermal process - Ng, C.K.; Ng, Z.L.; Ramesh, S.; Tan, C.Y.; Ting, C.H.; Chuah, Y.D.; Sutharsini, U. (University of Jaffna, 2020)
In this study, a facile hydrothermal method is applied to produce hydroxyapatite (HA) particles using egg shells as calcium precursors and fruit waste extracts (ba nana peel) as biomolecular templates at 150 °C for a reaction time period of 12 hours (h) and 24 hours. The sintering of the green samples of hydroxyapatite were conducted at 1250 °C in air for 2 h. The results showed that pectin extracted from banana peel extracts assisted in regulating crystal growth to obtain homoge neous hydroxyapatite powder, with higher purity observed for 24 h hydrothermal reaction time. Fourier-transform infrared spectroscopy (FTIR) spectra revealed the presences of phosphate (PO43) and hydroxyl (OH-) groups in the powders.A rel-ative density of 89.6 % was achieved for sintered hydroxyapatite compacts pro duced via hydrothermal method for 24 h. The sintered body was characterized by having high Vickers hardness of 5.35 GPa and good fracture toughness of 1.23 MPapm, suitable for biomedical application.
Keywords: Hydroxyapatite; Bio-waste; Bio-ceramics; Hydrothermal; Mechanical properties